INTEGRATING TECHNOLOGY IN MODERN EDUCATION AS AN EFFORT TO IMPROVE EFFECTIVE LEARNING IN THE ERA OF INDUSTRIAL REVOLUTION 5.0 - Loso Judijanto; Richa Fionasari; Nur Aziza Komalasari (Adisam Publisher, 2024)
Integrating technology in modern education is a crucial step to increase learning effectiveness, especially in the era of Industrial Revolution 5.0. Integrating technology in education is an important step to create learning that is more effective and relevant to the needs of the times. With the right strategy, technology can be a powerful tool for improving the quality of education and preparing students to face future challenges. Integrating technology in education is an important step to support learning transformation in the Society 5.0 era. As a teacher in this era, technology is not just an additional tool but an integral component of the learning process. To achieve wise and effective technology integration, teachers need to consider several tips for success that are in line with the principles of Independent Curriculum and Independent Learning. Modern education in the Industrial Revolution 5.0 era faces new challenges and opportunities in preparing students to face rapid and complex changes. The integration of technology in education can be an effort to increase effective learning.